PROFESSIONALISM COMPETENCY OF PUBLIC ISLAMIC SENIOR HIGH SCHOOL (MAN) TEACHERS IN WELCOMING THE ERA OF THE INDUSTRIAL REVOLUTION 4.0 IN ACEH - Fithriani, Fithriani; Darmiah, Darmiah; Walidin AK, Warul; Syabuddin, Syabuddin; Sulaiman, Sulaiman (Islam Futura, 2024)
This study aimed to determine the professional competence of teachers of the Public Islamic Senior High School ((known as Madrasah Aliyah Negeri or MAN) in welcoming the industrial revolution 4.0 era in Aceh. This qualitative research involve three principals and 60 teachers from three schools in Aceh who were selected purposively. Data analysis was carried out using a descriptive approach. The results showed that the professionalism of MAN teachers in Aceh in welcoming the industrial 4.0 era was good. It was indicated by teachers' skills in planning learning implementation plans, utilizing web-based media, using various teaching methods, using a student-centered approach, using cooperative learning models, and developing learning interactions. The professionalism of  MAN teachers in Aceh has implications for improving the quality of learning, indicated by an increase in learning motivation and an increase in student participation in learning. Teachers' strategy in developing teacher professionalism in welcoming the industrial 4.0 era was carried out by pursuing a master's degree and a teacher professional development training program.